Analisis Tata Fisik Candi Jedong dari Sudut Pandang Prinsip Desain Arsitektur - Hidayat, Anas; Setiadi, Y.A. Widriyakara (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2021)
Title: Analysis of the Physical Arrangement of Jedong Temple from the Point of view of Architectural Design Principles Jedong Temple, which is located in Wotan Mas village, Ngoro sub-district, Mojokerto regency, is a temple that spans a very long period, from the ancient Mataram era in Central Java to the Majapahit era in East Java. This unique temple is made from a mixture of stone and brick. The rocks are andesite and temple stones, while brick is a terracotta-colored burnt brick (the soil color). This research uses a comparative-critical method, comparing Jedong temple with similar temples or buildings. With this comparison, it will be able to reveal the architectural aspects that have not been revealed so far. Several architectural findings can be shown from this temple, among others, which indicates that this is a water structure, a building built on water or surrounded by water. Jedong Temple is in the form of 2 padhuraksa, which allegates other padhuraksa based on the symmetrical balance principle of padhuraksa in different temples. Then, access to the springs as the central axis or axis in a straight line. Also, the sequence of space division distinguishes between the outside space and the higher one in the hierarchy. Architecturally, Jedong temple shows that architectural principles have been applied since in the past, which we can use as materials to enrich architectural design principles in the present (the contemporary era).